1999
DOI: 10.1152/ajpendo.1999.276.5.e977
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of intracellular triglyceride stores by H spectroscopy: validation in vivo

Abstract: We validate the use of 1H magnetic resonance spectroscopy (MRS) to quantitatively differentiate between adipocyte and intracellular triglyceride (TG) stores by monitoring the TG methylene proton signals at 1.6 and 1.4 ppm, respectively. In two animal models of intracellular TG accumulation, intrahepatic and intramyocellular TG accumulation was confirmed histologically. Consistent with the histological changes, the methylene signal intensity at 1.4 ppm increased in both liver and muscle, whereas the signal at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
630
4
8

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(680 citation statements)
references
References 53 publications
38
630
4
8
Order By: Relevance
“…Quantitation of steatosis using 1 H MRS or MRI was closely correlated with histological assessment in patients with chronic liver disease of varying etiology and severity, and serial examinations showed a reduction in hepatic fat content with weight loss. This is consistent with previous studies reporting a correlation between MRS and histomorphometric data (9,10,24).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Quantitation of steatosis using 1 H MRS or MRI was closely correlated with histological assessment in patients with chronic liver disease of varying etiology and severity, and serial examinations showed a reduction in hepatic fat content with weight loss. This is consistent with previous studies reporting a correlation between MRS and histomorphometric data (9,10,24).…”
Section: Discussionsupporting
confidence: 93%
“…Results of MRS have shown to correlate closely with biochemical and histological assessments of liver triglyceride content (9,10), and to demonstrate a decrease in liver fat content following rosiglitazone therapy (11) or weight reduction (12,13). Other imaging modalities, such as ultrasonography and computed to-mography (CT), provide limited quantitative assessment (14,15).…”
mentioning
confidence: 99%
“…IMCL (85 ms) and EMCL (75 ms) T 2 relaxation times measured in this study match lipid T 2 relaxation values reported in the literature. 14 In concurrence with other studies, the overall lipid, IMCL and EMCL content in our study were expressed as a ratio using the spectral water peak as an internal reference. 6 …”
Section: Discussionsupporting
confidence: 88%
“…In consequence, a total of four 1 H-MR spectra (two with and two without water suppression) were collected for each observation, utilizing the proton signal from water in cardiac tissue as an internal reference for chemical shift offset and fat concentration ( • " Fig. 2a) [3, 13,14].…”
Section: Cardiac Mrsmentioning
confidence: 99%